Refugees or Victims of Human Trafficking? The case of migrant domestic workers in Hong Kong - Anderson, Jade; Li, Annie (Anti-Trafficking Review, 2018)
China is party to the 1951 Refugee Convention and the 2000 UN Trafficking Protocol, but has not extended coverage of either of the treaties to the Hong Kong Special Administrative Region of China (Hong Kong). Hong Kong does however offer non-refoulement protection on the basis of risks of torture or persecution. Further, Hong Kong legislation defines human trafficking, albeit only in terms of cross-border sex work. Victim identification also remains inadequate. The limited extant protection systems for refugees and victims of human trafficking operate separately and assume that such people are distinct with respect to their experiences and needs. These practices are often mirrored in the approaches of NGOs working in the city. Based on research undertaken by Justice Centre Hong Kong, this paper argues instead that boundaries between the two categories are blurry. The paper focuses on migrant domestic workers who may have claims to asylum and may be at the same time victims of human trafficking. It explores some of the implications for NGOs trying to secure better protections for such groups in Hong Kong. The paper concludes that siloing the refugee and the human trafficking frameworks creates a protection gap, particularly for people who enter Hong Kong as migrant domestic workers and cannot return home because they face a risk of persecution or torture.